Effect of language of instruction and pupils' attitude on the performance of primary school pupils in mathematics (2013)
This study investigated the effects of language of instruction, numerical ability and pupils' attitudes on the achievement of primary school pupils in mathematics. The study is quasi-experimental, using a 3 x 2 x 2 factorial design. Multistage sampling technique was adopted in selecting six Primary schools from three randomly selected Local Government Areas in Oyo central Senatorial zone of Oyo state where intact class of primary five pupils were used. The data collected were analysed using Analysis of Covariance. Seven research questions were stated and answered with significance level set at 0.05. The findings showed that there is significant main effect of treatment on pupils' achievement in mathematics, the pupils that were taught with Yoruba language performed better in Mathematics than the group that was taught with English language only and the group taught with combination of Yoruba and English languages. However, numerical ability and pupils' attitude did not significantly contribute to students' mathematics achievement in this study. It is therefore recommended that government should formulate and enforce a policy that, mother tongue or the language of immediate environmnet should be the language of instruction in mathematics class for all primary school pupils in order to lay good foundation for this subject right from primary school. Mathematics textbooks should be written either in the pupils' mother tongue (MT) or language of immediate community (LIC)